Josef Strauss Chronologisch-thematisches Werkverzeichnis - Doerner, Wolfgang (2021)
The catalogue of works lists all compositions of Josef Strauss (published in print as well as all existing manuscripts), including details of instrumentation, incipits, information of first performances and sources. The introductory chapter provides an extensive overview about specific items such as development of the dance music, instruments and publishers.